The Trend of “Awareness to Educational Changes” in years 2021- 2022: Bibliometrics Reviews - Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2022)
The research aims to provide knowledge about The Trend of “Awareness to Educational Changes” in years 2021- 2022. Preliminary results were gathered from a survey offered to 182 departments of four universities. The researcher used a definition and interpretation approach qualitative by using VOSviewer. A study was conducted based on Kohlberg's theory's concept of gender identity. Findings show that thelevel of education awareness has not been maximized in the process of face-to-face and online interaction activities. If the education system is managed properly, it will encourage learning in the context of interaction to run smoothly according to the concepts of educational theorists